Proposta de um modelo de maturidade para avaliação das práticas de eco-inovação nas organizações: eco-mi - Xavier, Amanda Fernandes (2017)
The urgency for sustainable changes in product performance and around the processes of the different organizational areas highlights the potential of eco-innovation as a management strategy. However, this holistic perspective of eco-innovation is still a challenge for companies, which face organizational barriers to the implementation of ecoinnovation related to strategy, structure, resources and culture; and operational barriers to implementation and global integration of eco-innovation, such as the absence of models, methods and supporting tools. Maturity approaches and prescriptive methods of evaluating eco-innovation are scarce. In order to overcome these barriers, this research proposes an Eco-Innovation Maturity Model (Eco-Mi), with the aim of systematizing ecoinnovation practices and providing a guide to holistic integration and evolution of organizational maturity. Based on a review of the literature, it was possible to develop the first version of the Eco-Mi Model, consisting of a Guide to good eco-innovation practices, Eco-innovation Maturity Levels and an Application Method. The Model was improved through expert evaluation using the Delphi Method, which allowed to increase its validity and reliability. Subsequently, the final version of the Eco-Mi was verified empirically through a case study. The results confirm the research hypothesis and therefore, the validity of the Eco-Mi Model as support for the integration and evolution of ecoinnovation in organizations and as a reference for the field of knowledge.